Economic Efficiency of Malaysian Oleochemical Enterprises - Ahmed Bushara, Mohamed Osman (2001)
This study comprises a rigorous Micro Econometric and Data Envelopment Analysis (DEA) of the performance of the Malaysian oleochemical enterprises over time. The analysis covers the following sectors: coconut oil, palm oil, palm kernel oil and other oils and fats, as well as twelve out of fifteen working oleochemical enterprises. The micro-economic data were graciously provided by Malaysian National Productivity Corporation (NPC), Malaysian Department of Statistics and some other respected sources: Panel data have been used in this study. The time series data and cross section data have been both pooled together to constitute panel data. Also maximum likelihood estimation has been incorporated for composed error models as well as DEA. Where appropriate, the literature has been updated. This study shows that the major advantage of the systematic application of the two frontier approaches, which are stochastic and deterministic (DEA), with multiple techniques on panel of data containing two levels, enables the comparison of synthesis of the results obtained to provide a comprehensive, detailed and insightful understanding of the producer behaviour. This approach is superior and informative than single eyed approaches. The results from all approaches consistently show that scale inefficiency and allocative inefficiency are the main problems in efficiency analysis. The scale inefficiency is mainly due to production operation at increasing returns to scale. This is noted specially in the coconut oil sector, the palm kernel oil sector and oleochemical enterprises. Allocative inefficiency is mainly due to under-utilisation of inputs relative to capital. Labour was under-utilised relative to capital in palm oil and other fat and oil sector. Allocative inefficiency due to underutilsation of inputs relative to capital is proved in this study. It is in consistent with that found by Seale (1990) in Egyptian Tileries, who claimed that Tileries on average were allocatively inefficient, employing too much capital relative to labour. The estimate of Malaysian oil and fat industry's total factor productivity (TFP) change is -3.705% for the period 1985 to 1996. The major contributor to this negative technological change is the palm oil sector and other oil and fat sector. The palm oil sector's negative contribution is at an average annual rate of 6.818% over the period of this study and other oil and fat sector is at an average annual rate of 5.8] 8%. This implies that the palm oil sector is ailing due to technological regress. It could be concluded that allocative efficiency requires first or second best pricing of final products; scale efficiency requires limitation on sub-optimal entry to the industry; technical efficiency requires cost minimisation by the incumbent firms; and finally product choice and dynamic efficiency require innovation by incumbents and new entrants.